(untitled) (Innovaciones Educativas, 2025)
The 21st century has proven to bring countless paradoxes into our daily lives that are difficult to explain or recognize in traditional terms. Current, ever-changing scenarios compellingly present realities filled with uncertainty. Furthermore, the innumerable reports, publications, and accounts on digital transformation in education is abundant; in some cases, they are profound, multidimensional, and innovative; in others, merely descriptive, segmented, and linear. In contrast, educational systems and school institutions continue to face a constant multifaceted challenge: how to avoid repeating formulas that biasedly prioritize the tools or devices themselves, instead of the pedagogical approach and the relational factor that humanizes any educational act? In the face of pedagogical urgencies, the immediate response that arises is—paradoxically—the "immediacy" in the use of technologies in training processes as an element that guarantees access, reach, participation, and educational continuity. In this overpopulation of information, in what could almost be called an unbreakable "noise," perhaps doubt, pause, and critical reflection on pedagogical practice, its environments, and its multiple factors constitute the disruptive approach element that allows expanding stances which include perspectives in search of solutions that, although absolutely urgent, require a view that contemplates the complex realities of current contexts to provide answers to the crisis.